Correlación de variables climáticas (temperatura y precipitación) con el índice de cobertura vegetal con el método ndvi en la zona noroccidental de la provincia de Cotopaxi en el piso bioclimático, bosque siempre verde piemontano de cordillera occidental de los andes comprendido entre 300 y 1400 msnm. - Velasco Tobar, Jerson Paul (2019)
The project was established in the parallel correlation between the index of plant coverage over time and the different climatic variables such as temperature, precipitation through which, the Gaussen diagram was developed that allowed us to know the climate variability established in previous years, for which it was based on satellite images that allowed to establish comparisons that allow to define the variation of the vegetation cover in the forest BsPn01. In this virtue, it was established that there is no influence of climatic factors (temperature and precipitation), with the variation of vegetation cover, generating new spaces of future research related to climate variables that allow establish principles of conservation and adaptation of species in the Sector. The results of the Gaussen diagram were observed that there was an inverse displacement of the wet season towards the dry season of approximately 38 days, this took place in the July month in the period 1995-2004; lasting until the third week of June (in the period 2005-2014). Compared to the maps drawn with the NDVI index in the ARCGIS program, it was possible to obtain that in the year 1990 there was a greater amount of wet forest in the study area, as the years pass according to the map of 2008 it can be observed that there is deforestation in areas where protection existed, due to the advance of the agricultural border. According to the 2016 map it can be corroborated that there is an increase in plant cover compared to the past years, which is due to the increase of a constant temperature and high humidity that the plant cover is increased.